VTR: A Web Tool for Identifying Analogous Contacts on Protein Structures and Their Complexes - Pimentel, Vitor; Mariano, Diego; Cantão, Letícia Xavier Silva; Bastos, Luana Luiza; Fischer, Pedro; de Lima, Leonardo Henrique Franca; Fassio, Alexandre Victor; Melo-Minardi, Raquel Cardoso de (Frontiers in Bioinformatics, 2021)
Evolutionarily related proteins can present similar structures but very dissimilar sequences. Hence, understanding the role of the inter-residues contacts for the protein structure has been the target of many studies. Contacts comprise non-covalent interactions, which are essential to stabilize macromolecular structures such as proteins. Here we show VTR, a new method for the detection of analogous contacts in protein pairs. VTR web tool performs structural alignment between proteins and detects interactions that occur in similar regions. To evaluate our tool, we proposed three case studies: (i) we compared a vertebrate myoglobin and a truncated invertebrate hemoglobin; (ii) analyzed interactions between the spike protein RBD of SARS-CoV-2 and the cell receptor ACE2; and (iii) compared a glucose-tolerant and a non-tolerant β-glucosidase enzyme used for biofuel production. The case studies demonstrate the potential of VTR for the understanding of functional similarities between distantly sequence-related proteins, as well as the exploration of important drug targets and rational design of enzymes for industrial applications. We envision VTR as a promising tool for understanding differences and similarities between homologous proteins with similar 3D structures but different sequences. VTR is available at http://bioinfo.dcc.ufmg.br/vtr.